Shaking table tests of tunnel linings in progressive states of damage. (August 2015) - Wang, Z.Z.; Jiang, Y.-J.; Zhu, C.A.; Sun, T.C.
Highlights: A method to identify the damage in the tunnel linings was proposed. The comparision between real field behavior and model behavior were conducted. The dominant frequencies decreased with an increase of the input PGA. Consecutive phases of damage for the tunnel linings were explained. Abstract: Tunnels have long been assumed to be able to withstand earthquakes and suffer little damage. However, investigations of tunnels after the Wenchuan earthquake in China revealed that over 30 tunnel linings were cracked. Different types of cracks were found in almost all the tunnel linings. In this study, a series of shaking table tests were conducted on scaled tunnel models under seismic excitations with increasing intensities. White noise sweep tests were interlaced with the seismic excitations to identify the damage in the tunnel linings. The accelerations and strains of the tunnel lining were measured. The test results are discussed based on the dominant frequencies, amplification factor, and lining strains. Furthermore, this paper presents the results of damage identification for various states of damage using the white noise sweep method. The dominant frequencies decreased with an increase of the input peak ground acceleration (PGA), which also reflected the damage of the tunnel lining. The dominant frequencies decreased by approximately 32% for an input PGA intensity of approximately 0.6 g, but the first cracks could still be visually detected. The cracks gradually propagate with the PGA increasing from 0.6 to 0.8 g. The effect of lining damage on the seismic performance of tunnel linings should be considered in the seismic design of tunnels.